AGRO SAFARI - Freitas, Bruno Henrique Soares de; Silva, Cálamo Andret da; Almeida, Gabriel de Souza; Chaves, Lucas Rodrigues; Santos, Luis Eduardo Godinho; Silva, Victor Henrique Fernandes; Junior, William Pereira (CIPEEX, 2022)
CURRENTLY, WITH THE ADVENT OF TECHNOLOGY, MORE AND MORE MODERN TECHNOLOGIES ARE AVAILABLE AND INNOVATIVE SOLUTIONS, WHETHER THROUGH SMARTPHONES, TABLETS OR COMPUTERS, AND THESE ARE USED TO FACILITATE OUR DAY TO DAY, BOTH IN THE CITY AND IN THE COUNTRYSIDE. MAKE GOOD USE OF THE TECHNOLOGICAL RESOURCES THAT ARE AVAILABLE, CAN MAKE PROFESSIONALS, MAINLY IN AGRIBUSINESS, INCREASE THEIR PRODUCTION EFFICIENCY, SAVE TIME AND GET THE BEST POSSIBLE FINANCIAL RETURN. IN THIS BIAS, IT IS NECESSARY POINT OUT THAT, THROUGH AGRO SAFARI, IT WILL BE POSSIBLE TO CARRY OUT MORE EASILY AND PRACTICALLY THE MANAGEMENT OF THE MAIN AGRIBUSINESS PROCESSES THROUGH THE RESOURCES MADE AVAILABLE WITHIN THE PLATFORM. THUS, IN ORDER TO PROMOTE GREATER INTERACTION BETWEEN TECHNOLOGY AND AGRIBUSINESS, THE DISCIPLINE OF INTERDISCIPLINARY PRACTICE: PROCESS MANAGEMENT CONTRIBUTED TO THE PROBLEMATIZATION AND MANAGEMENT OF THE PROJECT, THE PROGRAMMING LABORATORY DISCIPLINE CONTRIBUTED TO THE DEVELOPMENT AND IMPROVEMENT OF THE PLATFORM AND FINALLY THE DISCIPLINE OF ANALYSIS AND SOFTWARE DESIGN HELPED IN THE GATHERING OF REQUIREMENTS AND SCREEN PROTOTYPING.